2016
DOI: 10.1021/acsnano.6b00539
|View full text |Cite
|
Sign up to set email alerts
|

Improved In Vitro and In Vivo Biocompatibility of Graphene Oxide through Surface Modification: Poly(Acrylic Acid)-Functionalization is Superior to PEGylation

Abstract: The unique physicochemical properties of two-dimensional (2D) graphene oxide (GO) could greatly benefit the biomedical field; however, recent research demonstrated that GO could induce in vitro and in vivo toxicity. We determined the mechanism of GO induced toxicity, and our in vitro experiments revealed that pristine GO could impair cell membrane integrity and functions including regulation of membrane- and cytoskeleton-associated genes, membrane permeability, fluidity and ion channels. Furthermore, GO induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
214
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 342 publications
(245 citation statements)
references
References 52 publications
(117 reference statements)
17
214
1
4
Order By: Relevance
“…In contrast, GO was well dispersed in water and culture medium with the hydrodynamic size from 200 to 270 nm (Supplementary Figure S5), consistent with previous reports. 9,10,46 Owing to the abundant oxygen-containing functional groups on its surface, GO exhibits excellent dispersity in water, which is a crucial prerequisite for its biomedical applications. 21 As a result, MoS 2 /GO manifested great dispersity in water and cell culture medium with 10% FBS, similar to Lys-MoS 2 and FA-MoS 2 , and the hydrodynamic size was considerably reduced to 140-160 nm in water and 180-270 nm in culture medium, respectively (Supplementary Figure S5, Po0.05).…”
Section: Synthesis and Characterization Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, GO was well dispersed in water and culture medium with the hydrodynamic size from 200 to 270 nm (Supplementary Figure S5), consistent with previous reports. 9,10,46 Owing to the abundant oxygen-containing functional groups on its surface, GO exhibits excellent dispersity in water, which is a crucial prerequisite for its biomedical applications. 21 As a result, MoS 2 /GO manifested great dispersity in water and cell culture medium with 10% FBS, similar to Lys-MoS 2 and FA-MoS 2 , and the hydrodynamic size was considerably reduced to 140-160 nm in water and 180-270 nm in culture medium, respectively (Supplementary Figure S5, Po0.05).…”
Section: Synthesis and Characterization Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…Of note, unlike other nanomaterials, graphene oxide (GO) is able to localize in the lung through various exposure routes (for example, intravenous (i.v.) administration), [9][10][11][12] being ascribed to the formation of GO-protein complexes that were readily caught by lung capillary vessels. [13][14][15] GO's selective localization in the lung distinguishes it from other types of nanomaterials (mostly in liver and spleen), 16,17 offering a 'guided missile' to target the lung.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the diagnosis of GO/AgNPs to renal dysfunction would have important clinical and research significance. Previously, many works [33,34,37,[51][52][53] have been reported that GO can be gradually cleared by both renal excretion, meaning that GO/AgNPs have great potential in diagnosis and treatment of the nephropathy. As can be seen from Figure 6A, after intravenous administration with 0.5-10 mg per kg bw of GO/AgNPs for 36 h, the highquality renal imaging can be clearly observed by enhanced-CT under the protection of 20 mg per kg bw simvastatin.…”
Section: Ct Imaging Of Go/agnps In Vivomentioning
confidence: 99%